Analisis Penerapan Teknologi Web3.0 pada Pengembangan Game: Systematic Literature Review - Sama, Hendi; Liang, Suwarno; Khomali, Carlos Justin (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The development of Web3.0 technology in the gaming industry is showing significant and promising progress. Web3.0 offers innovation in game development through the application of blockchain, NFT, and metaverse technologies. This research aims to identify applications of Web3.0 technologies that are commonly used in game development and analyze the challenges and opportunities faced. The Systematic Literature Review (SLR) method was chosen to review the literature relevant to the application of Web3.0 in gaming. The results of this study cover the various technologies and platforms used, as well as challenges such as cost and scalability, and opportunities arising from digital ownership and new business models. The findings are expected to provide guidance for game developers in adopting Web3.0 technologies effectively and innovatively.